Reflections from five years of Sonic Interactions in Virtual Environments workshops. Issue 1 (1st January 2020) - Serafin, Stefania; Avanzini, Federico; De Goetzen, Amalia; Erkut, Cumhur; Geronazzo, Michele; Grani, Francesco; Nilsson, Niels Christian; Nordahl, Rolf
Abstract : For the past five years, the authors have been running at the IEEE Virtual Reality Conference a Workshop called Sonic Interactions in Virtual Environments (SIVE). The main goal of the workshop series has been to increase among the virtual reality community awareness of the importance of sonic elements when designing multimodal and immersive virtual environments. Starting from this experience, this paper presents a survey of the main active research topics related to sound in virtual and augmented reality (VR/AR), ranging from basic research in spatial audio rendering and sonic interaction design to applications in interactive environments for training, health, rehabilitation, entertainment, and art. Looking at the different research topics emerging from laboratories worldwide, the paper discusses how different research communities can collaborate and benefit from each other in order to increase sound awareness in VR and AR.